The political elite and the issue of sustainable human development in Iraq after 2003, a descriptive-analytical study - Ibrahim, Dr. Nazim Nawaf (The International and Political Journal, 2023)
Those who observe the history and development of human societies will find that societies, in their existence and stability, have witnessed that political power cannot be exercised by everyone, meaning that there must be a class or a minority to whom the leadership tasks are assigned in making decisions for their people. This category was called the political elite. As for the issue of development, it has witnessed wide interest from specialists, especially sustainable human development, which has become a pivotal issue in the countries of the world of the South, including Arab societies, and specifically Iraq, the subject of research, and this matter requires setting up a successful sustainable development project that achieves the interest of all.